UNDERSTANDING AUDIT METHODS TO ASSIST PLANNING ON PROGRAM EVALUATION: SHARING GAOâS EXPERIENCE ON NATIONAL HEALTH SECURITY PROGRAM - Adnyana, I Gede Sudi (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2017)
BPK has a mandate to conduct performance auditÂ for examining whether government agencies have implemented their critical programs in thepossible aspects of efficiency, effectiveness orÂ economy. Nevertheless, the current audit methodsÂ for those government programs designed at theplanning stages by the audit teams has not beenÂ fully emphasized on one or a combination of four main types of evaluation, such as process and/orimplementation evaluation; outcome evaluation; impact evaluation; and cost-benefit and cost effectivenessÂ analyses. They can be identified byusing measures of program performance, alongÂ with other information, to study the benefits of a program or how to improve it. The programÂ chosen is the NHS program, evaluated byÂ using GAOâs experience which wereÂ empiricallyÂ implemented and observed by the author duringÂ the fellowship program in the Agency. This study discusses the evaluation of FOD evaluation andÂ general guide to address researchable questionsderived from NHS program stage evaluation,Â analysis of researchable question types, andÂ to consider some challenges at designingÂ evaluations. Further, BPK could improveÂ methods and design of its performance audit planÂ as regards program evaluation by consideringÂ such variables that have been applied in theirbest practices.